Mathematics education journal - Universitas Muhammadiyah Malang. Program Studi Pendidikan Matematika (Department of Mathematics Education, University of Muhammadiyah Malang, 2017)
Methods and analysis of learning in the field of mathematics.
Keywords: Mathematics : Study and teaching : Periodicals; Mathematics : Study and teaching : Indonesia : Periodicals; Mathematics : Study and teaching; Indonesia